Improved sandy soil cementation effect evaluation method based on microstructure characteristics

By designing an improved cementing effect evaluation method based on microstructure characteristics, the problem of insufficient research on the microstructure of cemented soil in the prior art is solved, and quantitative evaluation of soil cementing effect and optimized selection of polymer dosage are achieved.

CN119643282AActive Publication Date: 2025-03-18HOHAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411689810.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

When studying the microstructure of cemented soil, the prior art mainly focuses on its influence on the mechanical properties and water-based properties of the soil, ignores the study of the microstructure itself, and lacks methods to quantitatively evaluate the cementing effect of soil.

Method used

A method for evaluating the cementing effect of sand and soil based on microstructure characteristics is designed. By collecting samples of cemented soil and plain soil, performing indoor tests of mechanical and hydrologic characteristics, combining three-dimensional surface measurement, SEM image analysis, CT test and other means, the mechanical friction coefficient, pore characteristic coefficient and cementing coefficient of cemented soil are calculated to quantitatively evaluate the cementing effect of soil.

Benefits of technology

Quantitative evaluation of soil cementation effect is achieved, and the advantages and disadvantages of different polymers on soil improvement effects can be evaluated through microstructure characteristic parameters and indoor test results, and the optimal mixing amount selection of polymers can be guided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643282A_ABST
    Figure CN119643282A_ABST
Patent Text Reader

Abstract

The invention discloses an improved sandy soil cementation effect evaluation method based on microstructure characteristics, which comprises the following steps: carrying out indoor test on a cementation sample and a plain soil sample to obtain the mechanical strength improvement rate and the hydraulic strength improvement rate of the cementation soil sample; carrying out three-dimensional surface measurement on the damaged section caused by the indoor test, collecting an SEM image of the damaged section, obtaining the micromechanical characteristics of the cemented soil body sample, and calculating the mechanical friction resistance coefficient of the damaged section of the cemented soil body sample; performing a CT test on the cemented soil body sample to obtain micro-pore characteristics of the cemented soil body sample; and calculating the cementation coefficient of the cemented soil body sample so as to quantitatively evaluate the cementation effect of the soil body. The improvement effect of the cemented soil body is evaluated in combination with macroscopic and microscopic levels, and the advantages and disadvantages of the cementing effect of the soil body are quantitatively evaluated by expressing the cementing coefficient. According to the method, microstructure information transmitted by the SEM image can be quantitatively expressed, and determination of the optimal mixing amount of the high polymer is guided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of engineering geology, and in particular to a method for evaluating the cementation effect of improved sand based on microstructural characteristics. Background Art

[0002] Natural soil is widely used as a natural foundation filler in the engineering field, but its poor engineering properties often lead to disasters such as uneven ground settlement and ground fissures, and some necessary reinforcement measures are needed for natural soil. At present, bio-glue and other polymers are often used to improve soil. The cementing effect of polymers can fill the pores of soil, bridge and wrap soil particles, and cement the loose soil particles together, thereby achieving a better improvement effect. The microstructural characteristics of cemented soil can be intuitively obtained by using CT, NMR and SEM techniques, but the current research on the microstructure of cemented soil focuses on its influence on the mechanical properties and hydraulic properties of cemented soil, ignoring the research on the microstructure of cemented soil itself. There are few studies on the cementing effect of modified soil through microstructure, and there is a lack of a method for quantitatively evaluating the advantages and disadvantages of soil cementing effect. Therefore, the present invention proposes a method for evaluating the cementing effect of improved sand based on microstructural characteristics. Summary of the invention

[0003] The purpose of the present invention is to provide a method for evaluating the bonding effect of improved sand based on microstructural characteristics, which can quantitatively evaluate the quality of the soil bonding effect.

[0004] In order to achieve the above functions, the present invention designs a method for evaluating the cementation effect of improved sand based on microstructural characteristics. For the target soil, the following steps S1 to S5 are performed to complete the quantitative evaluation of the cementation effect of the soil:

[0005] Step S1: collecting cemented soil samples and plain soil samples of the target soil body, and performing indoor tests on the mechanical characteristics of the cemented soil samples and the plain soil samples, including unconfined compression test, direct shear test and tensile test, to obtain the mechanical strength improvement rate of the cemented soil samples, including the improvement rate of compressive strength, shear strength and tensile strength;

[0006] Step S2: perform three-dimensional surface measurement on the failure section caused by the indoor test of the cemented soil sample, collect the SEM image of the failure section, simulate the indoor test results of the mechanical characteristics, obtain the microscopic mechanical characteristics of the cemented soil sample, including the fluctuation degree, roughness, cementation rate and particle cohesion of the failure section, and further calculate the mechanical friction coefficient of the failure section of the cemented soil sample;

[0007] Step S3: performing indoor tests on hydraulic characteristics of the cemented soil sample and the plain soil sample, including evaporation cracking test, scour test and disintegration test, respectively, to obtain the hydraulic strength improvement rate of the cemented soil sample, including scour reduction rate and crack area reduction rate;

[0008] Step S4: performing a CT test on the cemented soil sample to obtain the microscopic hydraulic characteristics of the cemented soil sample, including porosity, connected porosity, isolated porosity and pore coordination number, and further calculating the pore characteristic coefficient of the cemented soil sample;

[0009] Step S5: According to the mechanical strength improvement rate of the cemented soil sample and the mechanical friction coefficient of the failure section of the cemented soil sample; according to the hydraulic strength improvement rate of the cemented soil sample and the pore characteristic coefficient of the cemented soil sample, the cementation coefficient of the cemented soil sample is calculated to quantitatively evaluate the soil cementation effect.

[0010] Beneficial effects: Compared with the prior art, the advantages of the present invention include:

[0011] 1. The present invention can evaluate the improvement effect of different polymers on soil by combining the microstructural characteristic parameters of different polymer-bonded soil and the indoor test results;

[0012] 2. The present invention performs digital analysis on SEM image information, quantitatively expresses the microstructure information transmitted by the SEM image, and determines the optimal doping amount of the polymer through guidance of the microstructure information. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a flow chart of a method for evaluating the cementation effect of improved sand based on microstructure characteristics provided in an embodiment of the present invention;

[0014] Figure 2 is a dyed SEM picture of a failure cross section of a cemented soil sample provided in an embodiment of the present invention;

[0015] Figure 3 is a pore coordination number distribution diagram provided according to an embodiment of the present invention. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0017] An improved sandy soil cementation effect evaluation method based on microstructure characteristics is provided in an embodiment of the present invention. Figure 1 , perform the following steps S1 to S5 to complete the quantitative evaluation of the soil bonding effect:

[0018] Step S1: Collect cemented soil samples and plain soil samples of the target soil, and conduct indoor tests on the mechanical characteristics of the cemented soil samples and the plain soil samples, including unconfined compression test, direct shear test and tensile test, to obtain the mechanical strength improvement rate of the cemented soil samples, including the improvement rate of compressive strength, shear strength and tensile strength; to evaluate the improvement effect of the polymer on the mechanical properties of the soil.

[0019] The improvement rate Δq of the compressive strength of the cemented soil sample in step S1 is as follows:

[0020]

[0021] The increase rate Δu of the shear strength of the cemented soil sample is as follows:

[0022]

[0023] The increase rate Δv of the tensile strength of the cemented soil sample is as follows:

[0024]

[0025] In the formula, q 1 、u 1 and v 1 are the compressive strength, shear strength and tensile strength of the cemented soil sample, respectively, 0 、u 0 and v 0 They are the compressive strength, shear strength and tensile strength of the plain soil sample respectively.

[0026] Step S2: perform three-dimensional surface measurement on the failure section caused by the indoor test of the cemented soil sample, collect the SEM image of the failure section, simulate the indoor test results of the mechanical characteristics, obtain the microscopic mechanical characteristics of the cemented soil sample, including the fluctuation degree, roughness, cementation rate and particle cohesion of the failure section, and further calculate the mechanical friction coefficient of the failure section of the cemented soil sample;

[0027] The calculation steps of the fluctuation and roughness of the failure section of the cemented soil sample in step S2 are as follows:

[0028] Step S21: Use a white light interferometer to measure the elevation of the failure section, set the plane where the lowest point of the failure section is located as the zero elevation plane, and the maximum elevation is d max The fluctuation of the failure section is defined as d q =d max ;

[0029] Step S22: Divide the failure section into m regions on average. The value of m should be such that the fluctuation degree d of the failure section of each region is q Not more than 0.05mm;

[0030] Step S23: Select four points in each area and take the average height of the four points as the average height d of the area. n , where 1≤n≤m, n represents the nth region, and the roughness S of the damaged section u The definition is as follows:

[0031]

[0032] in,

[0033] The calculation steps of the cementation rate and particle cohesion of the cemented soil sample in step S2 are as follows:

[0034] Step S24: establishing a particle flow simulation model through the processes of sampling, preloading, bonding, unloading, loading plate and loading; the total number of particles in the particle flow simulation model should be no less than 6000, the soil particles are set as a parallel bonding model, and the soil particles and the loading plate are set as a linear model;

[0035] Step S25: calibrate the parameters of the particle flow simulation model by trial and error method. When the particle flow simulation result satisfies that the simulation curve has the same trend as the actual curve, the peak strength error is less than 10%, the peak strain error is less than 10%, and the elastic modulus error is less than 10%, the particle flow simulation result is considered to be valid and the parameter calibration is reliable, and the contact model parameters at this time are obtained;

[0036] Step S26: Process the SEM image of the fractured cross section of the cemented soil sample, referring to Figure 2 , respectively dyeing the soil particles and the colloid particles, and identifying the total area S of the soil particles through image processing software t , the total area of ​​the rubber particles S j , the cementation rate p of the failure section is as follows:

[0037]

[0038] Step S27: The particle cohesion of the broken section is defined as N = αS 1 +βS 2 , where S 1 S is the ratio of the area of ​​direct contact between soil particles and the area of ​​the failure cross section. 2 is the ratio of the contact area of ​​soil particles under cementation to the failure cross-sectional area, α is the effective modulus of the linear model in the particle flow software, and β is the effective modulus of the parallel bond model in the particle flow software.

[0039] The mechanical friction coefficient f of the failure section of the cemented soil sample in step S2 is as follows:

[0040]

[0041] in, is the bite coefficient of the failure section; is the bonding force of the failure section, and E is the elastic modulus of the cemented soil sample.

[0042] Step S3: Conducting indoor tests on hydraulic characteristics of cemented soil samples and plain soil samples, including evaporation cracking test, scour test and disintegration test, respectively, to obtain the hydraulic strength improvement rate of the cemented soil samples, including erosion reduction rate and crack area reduction rate, so as to evaluate the improvement effect of the polymer on the hydraulic properties of the soil.

[0043] The erosion reduction rate of the cemented soil sample in step S3 is Δb=b 1 -b 0 , the crack area reduction rate of the cemented soil sample where b 1 , p 1 is the erosion rate and crack area of ​​the cemented soil sample, b 0 , p 0 is the erosion rate and crack area of ​​the plain soil sample.

[0044] Step S4: performing a CT test on the cemented soil sample to obtain the microscopic hydraulic characteristics of the cemented soil sample, including porosity, connected porosity, isolated porosity and pore coordination number, and further calculating the pore characteristic coefficient of the cemented soil sample;

[0045] The porosity of the cemented soil sample in step S4 is defined as follows:

[0046]

[0047] Among them, V V and V T represent the pore volume and total soil volume, respectively;

[0048] The connected porosity and isolated porosity of cemented soil samples are defined as Among them, V l , V g represent the connected pore volume and isolated pore volume, respectively;

[0049] Reference Figure 3 The pore coordination number of the cemented soil sample is defined as Among them, N B is the number of branch pores connected to a node, N E is the number of endpoint pores, N J is the number of nodes, and the coordination number corresponding to the maximum percentage of the coordination number is C max .

[0050] The pore characteristic coefficient Q of the cemented soil sample in step S4 is as follows:

[0051]

[0052] Step S5: According to the mechanical strength improvement rate of the cemented soil sample and the mechanical friction coefficient of the failure section of the cemented soil sample; according to the hydraulic strength improvement rate of the cemented soil sample and the pore characteristic coefficient of the cemented soil sample, the cementation coefficient of the cemented soil sample is calculated to quantitatively evaluate the soil cementation effect.

[0053] The cementation coefficient L of the cemented soil sample in step S5 is as follows:

[0054]

[0055] Where Δu is the increase rate of shear strength, Δq is the increase rate of compressive strength, Δv is the increase rate of tensile strength, f is the mechanical friction coefficient of the failure section of the cemented soil sample, and Q is the pore characteristic coefficient of the cemented soil sample.

[0056] In one application example, the dry density of the soil sample is set to 1.62 g / cm 3 , moisture content is 23%, curing agent content is 0.5%, and curing age is 24h. By calculating and weighing a certain mass of curing agent, soil and water and fully mixing them to make a cemented soil sample, indoor tests were carried out and Δq = 19.44%, Δu = 12.36%, Δv = 28.83%, Δb = 41.68%, and Δp = 61.97% were obtained. The sample was subjected to a CT scanning test and the cemented soil sample n was obtained. l =27.66%, n g =2.67% and C max =10, Q = 2.14. The failure cross section of the cemented soil sample after the test was measured using a white light interferometer to obtain the failure cross section d q =d max =1.04mm, S u =0.44, f y =0.98; SEM images of the fractured cross section of the cemented soil sample were collected, the SEM images were preprocessed, and numerical tests were performed based on the indoor test results to obtain p = 1.8%, S 1 =0.04%, S 2 =0.11%, α=10 8 , β=3.65×10 7 , E = 2.14 × 10 6 , N = 8.02 × 10 4 , f j=0.15, f=0.33, L=0.82, and the cementation effect in the improved soil is quantitatively evaluated based on the value of L.

[0057] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for evaluating the cementation effect of improved sand based on microstructural characteristics, characterized in that: For the target soil, the following steps S1 to S5 are performed to complete the quantitative evaluation of the soil bonding effect: Step S1: collecting cemented soil samples and plain soil samples of the target soil body, and performing indoor tests on the mechanical characteristics of the cemented soil samples and the plain soil samples, including unconfined compression test, direct shear test and tensile test, to obtain the mechanical strength improvement rate of the cemented soil samples, including the improvement rate of compressive strength, shear strength and tensile strength; Step S2: perform three-dimensional surface measurement on the failure section caused by the indoor test of the cemented soil sample, collect the SEM image of the failure section, simulate the indoor test results of the mechanical characteristics, obtain the microscopic mechanical characteristics of the cemented soil sample, including the fluctuation degree, roughness, cementation rate and particle cohesion of the failure section, and further calculate the mechanical friction coefficient of the failure section of the cemented soil sample; Step S3: performing indoor tests on hydraulic characteristics of the cemented soil sample and the plain soil sample, including evaporation cracking test, scour test and disintegration test, respectively, to obtain the hydraulic strength improvement rate of the cemented soil sample, including scour reduction rate and crack area reduction rate; Step S4: performing a CT test on the cemented soil sample to obtain the microscopic hydraulic characteristics of the cemented soil sample, including porosity, connected porosity, isolated porosity and pore coordination number, and further calculating the pore characteristic coefficient of the cemented soil sample; Step S5: According to the mechanical strength improvement rate of the cemented soil sample and the mechanical friction coefficient of the failure section of the cemented soil sample; according to the hydraulic strength improvement rate of the cemented soil sample and the pore characteristic coefficient of the cemented soil sample, the cementation coefficient of the cemented soil sample is calculated to quantitatively evaluate the soil cementation effect.

2. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 1, characterized in that: The improvement rate Δq of the compressive strength of the cemented soil sample in step S1 is as follows: The increase rate Δu of the shear strength of the cemented soil sample is as follows: The increase rate Δv of the tensile strength of the cemented soil sample is as follows: Where q1, u1 and v1 are the compressive strength, shear strength and tensile strength of the cemented soil sample, respectively; q0, u0 and v0 are the compressive strength, shear strength and tensile strength of the plain soil sample, respectively.

3. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 1, characterized in that: The calculation steps of the fluctuation and roughness of the failure section of the cemented soil sample in step S2 are as follows: Step S21: Use a white light interferometer to measure the elevation of the failure section, set the plane where the lowest point of the failure section is located as the zero elevation plane, and the maximum elevation is d max The fluctuation of the failure section is defined as d q =d max ; Step S22: Divide the failure section into m regions on average. The value of m should be such that the fluctuation degree d of the failure section of each region is q Not more than 0.05mm; Step S23: Select four points in each area and take the average height of the four points as the average height d of the area. n , where 1≤n≤m, n represents the nth region, and the roughness S of the damaged section u The definition is as follows: in, 4. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 3 is characterized in that: The calculation steps of the cementation rate and particle cohesion of the cemented soil sample in step S2 are as follows: Step S24: establishing a particle flow simulation model through sample forming, pre-pressing, bonding, unloading, loading plate and loading processes; Step S25: calibrate the parameters of the particle flow simulation model by trial and error method. When the particle flow simulation result satisfies that the simulation curve has the same trend as the actual curve, the peak strength error is less than 10%, the peak strain error is less than 10%, and the elastic modulus error is less than 10%, the particle flow simulation result is considered to be valid and the parameter calibration is reliable, and the contact model parameters at this time are obtained; Step S26: Process the SEM image of the failure cross section of the cemented soil sample, dye the soil particles and the cement particles respectively, and identify the total area S of the soil particles through image processing software. t , the total area of ​​the rubber particles S j , the cementation rate p of the failure section is as follows: Step S27: The particle cohesion of the failure section is defined as N=αS1+βS2, where S1 is the ratio of the area of ​​direct contact between soil particles and the failure section area, S2 is the ratio of the contact area of ​​soil particles under cementation to the failure section area, α is the effective modulus of the linear model in the particle flow software, and β is the effective modulus in the parallel bonding model in the particle flow software.

5. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 4, characterized in that: The mechanical friction coefficient f of the failure section of the cemented soil sample in step S2 is as follows: in, is the bite coefficient of the failure section; is the bonding force of the failure section, and E is the elastic modulus of the cemented soil sample.

6. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 1, characterized in that: In step S3, the erosion reduction rate of the cemented soil sample is Δb=b1-b0, and the crack area reduction rate of the cemented soil sample is Where b1 and p1 are the erosion rate and crack area of ​​the cemented soil sample, and b0 and p0 are the erosion rate and crack area of ​​the plain soil sample.

7. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 1, characterized in that: The porosity of the cemented soil sample in step S4 is defined as follows: Among them, V V and V T represent the pore volume and total soil volume, respectively; The connected porosity and isolated porosity of cemented soil samples are defined as Among them, V l , V g represent the connected pore volume and isolated pore volume, respectively; The pore coordination number of a cemented soil sample is defined as Among them, N B is the number of branch pores connected to a node, N E is the number of endpoint pores, N J is the number of nodes, and the coordination number corresponding to the maximum percentage of the coordination number is C max .

8. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 7, characterized in that: The pore characteristic coefficient Q of the cemented soil sample in step S4 is as follows:

9. The method for evaluating the cementation effect of improved sand based on microstructural characteristics according to claim 1, characterized in that: The cementation coefficient L of the cemented soil sample in step S5 is as follows: Where Δu is the increase rate of shear strength, Δq is the increase rate of compressive strength, Δv is the increase rate of tensile strength, f is the mechanical friction coefficient of the failure section of the cemented soil sample, and Q is the pore characteristic coefficient of the cemented soil sample.

Citation Information

Patent Citations

  • Porous inorganic coating / polyolefin microporous membrane compound diaphragm and preparation method thereof

    CN102977394A

  • Soil material erosion test device and method

    CN114136824A

  • Model construction process and method for describing cementation contact of combustible ice sediments based on particle flow

    CN118410691A

  • Method for establishing relation between silt mechanical properties and silt microstructure

    CN118758777A